2015
DOI: 10.1039/c5em00073d
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of nonylphenol degradation in leafy vegetables using a deuterated tracer

Abstract: In this study, the residues of nonylphenol, an endocrine-disrupting chemical, were investigated in two types of leafy vegetables, leek and cabbage, that are commonly consumed in eight provinces in China. Nonylphenol was detected in 43.50% of the 223 samples, at concentrations up to 51.90 μg kg(-1). The isotopic tracer 4-n-NP-2,3,5,6-d4-OD was chosen to simulate the degradation of nonylphenol in cabbage. More than 80% of the tracer was degraded in the first 7 days, and most of it had vanished by the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Previous studies reported the presence of NP on various fruits and vegetables in China, Germany, Taiwan and the USA (Fang et al, 2015;Guenther et al, 2002;Lu et al, 2007Lu et al, , 2013Dodgen et al, 2013;She et al, 2012) (Table 1). All of these fresh products were obtained from producers or supermarkets, except for those analysed by Dodgen et al (2013), where the presence of NP was as a consequence of fortified incubation in the laboratory.…”
Section: Presence On Edible Cropsmentioning
confidence: 96%
See 4 more Smart Citations
“…Previous studies reported the presence of NP on various fruits and vegetables in China, Germany, Taiwan and the USA (Fang et al, 2015;Guenther et al, 2002;Lu et al, 2007Lu et al, , 2013Dodgen et al, 2013;She et al, 2012) (Table 1). All of these fresh products were obtained from producers or supermarkets, except for those analysed by Dodgen et al (2013), where the presence of NP was as a consequence of fortified incubation in the laboratory.…”
Section: Presence On Edible Cropsmentioning
confidence: 96%
“…Surfactants are also added to biocontrol products to enhance the effect of the biocontrol agent by contributing to adherence, spreading and enabling penetration (Singh et al, 2007). Following pesticide application, NP can still be detected on crops after 35 days (Fang et al, 2015).…”
Section: Agricultural Pesticides and Fertilizersmentioning
confidence: 99%
See 3 more Smart Citations